Design and synthesis of benzodiazepines as brain penetrating PARP-1 inhibitors. (31st December 2022) - Yu, Jiang; Gou, Wenfeng; Shang, Haihua; Cui, Yating; Sun, Xiao; Luo, Lingling; Hou, Wenbin; Sun, Tiemin; Li, Yiliang
Abstract: The poly (ADP-ribose) polymerase (PARP) inhibitors play a crucial role in cancer therapy. However, most approved PARP inhibitors cannot cross the blood-brain barrier, thus limiting their application in the central nervous system. Here, 55 benzodiazepines were designed and synthesised to screen brain penetrating PARP-1 inhibitors. All target compounds were evaluated for their PARP-1 inhibition activity, and compounds with better activity were selected for further assays in vitro . Among them, compounds H34, H42, H48, and H52 displayed acceptable inhibition effects on breast cancer cells. Also, computational prediction together with the permeability assays in vitro and in vivo proved that the benzodiazepine PARP-1 inhibitors we synthesised were brain permeable. Compound H52 exhibited a B/P ratio of 40 times higher than that of Rucaparib and would be selected to develop its potential use in neurodegenerative diseases. Our study provided potential lead compounds and design strategies for the development of brain penetrating PARP-1 inhibitors. HIGHLIGHTS: Structural fusion was used to screen brain penetrating PARP-1 inhibitors. 55 benzodiazepines were evaluated for their PARP-1 inhibition activity. Four compounds displayed acceptable inhibition effects on breast cancer cells. The benzodiazepine PARP-1 inhibitors were proved to be brain permeable. Graphical Abstract: UF0001